MECHANICAL ANALYSES OF THE EMPLACEMENT OF LACCOLITHS AND LOPOLITHS - Zenzri H.; Keer L.M. (My University, 2001)
Elastic deformations of host rocks during the emplacement within the Earth's crust of magmatic intrusions, such as laccoliths and lopoliths, are analyzed. The present analysis is built upon semianalytic elastic solutions for a pressurized horizontal crack buried between an overburden and a semi-infinite base. The current work improves upon recent analyses by including several important features inherent to the development of laccoliths and lopoliths. First, both elongated intrusions (plane strain case) and circular intrusions (axisymmetric case) are described by the current models. Second, the effect of the difference in elastic moduli between the overburden and the substrate is considered. This difference in elastic moduli is characterized by one of the Dundurs parameters. Third, the stress intensity factor at the tip of the crack is assumed to be zero. Thus the stresses are finite, and the obtained laccolithic shapes are doubly hinged with horizontal slopes at the peripheries, as observed in the field. Fourth, unlike plate bending models, which are commonly used for major laccoliths, the current models describe a full range of ratios of intrusion width to overburden thickness. Numerical results are obtained for different combinations of the geometrical parameters, the material contrast and the driving pressure distributions. Graphs of these results confirm the plate bending model for large laccoliths, support Gilbert's concept pertaining to small laccoliths, permit the prediction of the sill-laccolith transition, allow the analysis of the asymmetry in the vertical displacements above and below the intrusion, and lead to a possible mechanism of deep lopoliths emplacements. Some of the obtained results are compared to the available field data from the Henry Mountains.